Penerapan Kompres Tepid Water Sponge Terhadap Penurunan Suhu Tubuh Pada Anak Dengan Hipertermi Di Ruang Wijaya Kusuma RSUD Kardinah Kota Tegal - Riana, Maya Reza; Netra Wirakhmi, Ikit (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Hyperthermia can be defined as a condition of body temperature above normal as a result of an increase in the temperature control center in the hypothalamus. In children who have a fever, the temperature increase is mild, ranging from 37.5-38°C. The impact that can be caused if the fever is not treated is that it can cause brain damage, hyperpyrexia which will cause shock, epilepsy, mental retardation or learning disabilities. To overcome the problem of hyperthermia, several independent nursing actions can be carried out, one of which is the Tepid Water Sponge (TWS). This experiment aims to determine the effect of administering Tepid Water Sponge to patients with hyperthermia in the Wijaya Kusuma Room, Kardinah Tegal Hospital. This experiment was carried out with observations during 3 meetings and interventions for administering the Water Sponge Technique for 3 days on April 14-15, 2025. The results of the first experiment were that the patient's body temperature before being given Tepid Water Sponge was 39.8 Celsius, on the second day there was a decrease in body temperature to 38.2 Celsius, and on the third day the body temperature became 37.5 Celsius. In conclusion, Tepid Water Sponge therapy is effective in lowering body temperature in patients with hyperthermia in the Wijaya Kusuma Room, Kardinah Tegal Hospital.